Study of Structure and Educational Values in Lelakaq Sasak - Murtafi'ah, Wahidatul; Hendri (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
Lelakaq Sasak is part of old literature that is still developing among the Sasak people of Lombok. Lelakaq is a literary work of the people of Lombok, in which certain structures and values need to be preserved and emulated by the younger generation. This study uses descriptive qualitative research with data collection techniques used, namely observation techniques, interviews, and documentation. While the data analysis used is a qualitative descriptive analysis technique. From the results of the study, it was concluded that in lelakaq Sasak there is structure and educational value contained therein. The study of structure in lelakaq has typology, denotation, and connotation, lelakaq tends to use the word denotation and uses the word connotation a little. Imagery structures (images) in lelakaq use more imagery of feelings and sights. Poetry in lelakaq is more dominant in having cross rhymes, some are broken and parallel rhymes. Meanwhile, in terms of educational value, it can be found that lelakaq contains religious educational values, moral educational values, social educational values, and cultural educational values.